Prognostic Nutritional Index (PNI) at Admission Predicts In-Hospital Mortality of COVID-19-Infected Patients (Majalah Kedokteran Bandung, 2025)
Corona Virus Disease-2019 (COVID-19) was declared a pandemic in March 2020 and caused considerable deaths in all parts of the world. Mortality is influenced by the immune system status and increased vulnerability to infection, both related to nutritional status. The Prognostic Nutritional Index (PNI), calculated using lymphocyte count and albumin levels, may have the ability to more accurately characterize the nutritional and inflammatory conditions of COVID-19 patients. This retrospective study analyzed 967 COVID-19 patients at Ulin Hospital Banjarmasin, Indonesia, by examining demographic data, laboratory results, and PNI in relation to survival outcomes. The study revealed that factors such as age, sex, comorbidities (including hypertension, diabetes mellitus/DM, obesity, etc.), number of comorbidities, and disease severity correlated with mortality. Leucocyte count, lymphocyte count, albumin levels, and PNI all showed significant correlations with survival (p
Keywords: COVID-19; leucocyte; mortality; PNI; prognostic